Industrial Instruments RE-I Solu Bridge Controller
A Solu bridge determines the dissolved solids in water by measuring its conductivity. In 1965, Beckman Instruments acquired the Cedar Grove, New Jersey based Industrial Instruments, Inc.
Keywords: Scientific apparatus and instruments; Bridge circuits; Beckman Instruments, Inc.; Electronic circuits